The Association between Community Knowledge Level and Behavior on Dengue Hemorrhagic Fever Prevention in Tourism Area Celuk-Benoa, South Kuta Regency - Yuliantari, Putu Saras Widar; Damayanti, Putu Ayu Asri; Damayanti, Made Rini (Journal of A Sustainable Global South, 2022)
Abstract. Dengue Hemorrhagic Fever (DHF) is still endemic in Bali, including in the Banjar Celuk tourist area, Benoa Village, South Kuta. Mosquito control plays an important role in reducing DHF cases due to the absence of vaccines and drugs to date. Therefore this study was to determine the level of knowledge-behavior and their relationship of the community towards DHF prevention in Benoa. The study carried out in February-July 2019 with a cross sectional design. The relationship of community knowledge and behavior in the prevention of DHF was examined using the Chi-Square test. This study was followed by 68 subjects through simple random sampling technique. Result of the study were the most respondents aged 36-45 years in 23 (33.9%) subjects, education level senior high school in 35 (51.5%) subjects, and work as housewives in 22 (32,4%) subjects. The level of knowledge and behavior both were included in the category sufficient in 45 (66.2%) subjects and 40 (58.8%) subjects respectively. The chi-square analysis obtained that there was a relationship between the level of knowledge with behavior in the prevention of DHF (p value = 0.002) where the better of the knowledge would followed by better behavior.The conclusion: there was association between level of knowledge and subject's behavior in preventing DHF. The community knowledge and behavior still need to be improved through various health promotion programs to support tourism industry in Banjar Celuk, Benoa Village, South Kuta